Perioperative period from a pediatric perspective: a mixed-methods study - Selda Yüzer Alsaç; Gökçen Aydın Akbuğa (Frontiers in Pediatrics)
ObjectiveTo determine anxiety levels of children aged 8–12 years who were admitted to the pediatric clinic for surgery; to understand the anxiety and experiences in perioperative period, and to determine their physical and emotional needs in this process.MethodsThe research was carried out in the surgical ward of a public hospital between October 2023 and February 2024. A mixed research method (quantitative and qualitative) was used. In the first phase, the State Anxiety Inventory for Children was administered to evaluate preoperative anxiety levels. In the second phase, in-depth interviews were conducted with children to explore their perceptions and experiences regarding the surgical process.ResultsThe mean age of the children was 9.72 ± 1.38 years, and 74.6% of the participants were boys (N = 126). The mean anxiety score of the children was 38.39 ± 10.56. It was detected that the mean anxiety score of younger children was higher (p < 0.000). The mean anxiety score of children who underwent genitourinary system surgery was found to be higher than other types of surgery (p < 0.035). It was also determined that the mean anxiety scores were lower among children who were informed before the operations decreased (p < 0.003). After in-depth interviews with children (N = 12), the themes of “The Effect of Hospital and Operating Room Environment”, “Social Support” and “Expectations from the Operating Room” were determined.ConclusionThe quantitative results of the study indicate that variables such as age, type of surgery, whether the child was informed about the surgery make a difference in children's anxiety levels. The qualitative results of the study revealed that children felt anxiety and fear about the hospital and surgery environment at every stage of the perioperative period.